Tax Aspect, Governance Mechanism, and New Bank Discretion: Restructuring & Covid-19 Effect - Valdiansyah, Riyan Harbi; Hartati, Andi Neneng Sugi; Puspitasari, Diana (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This study investigates the influence of deferred tax expenses and tax retention on earnings management with banking governance mechanisms as moderating variables. The sample for this study comprises 124 data points from banks listed on the IDX between 2019 and 2022. The effects of credit restructuring and the global SARS-CoV-2 pandemic were examined using a moderated regression analysis with a fixed effect model (FEM). The results reveal that deferred tax expenses have a positive impact on discretionary provision, while tax planning has no effect. Additionally, an independent commissioner mitigates the positive effect of deferred tax expenses on earnings management. The study also finds a significant difference in earnings management practices between the pre-Covid-19 period and pandemic periods. These findings suggest that regulators and banking risk control teams should be cautious about tax aspects that may encourage discretionary behavior such as deferred tax liabilities and tax planning during specific periods. Keywords: Deferred Tax Expense, Tax Retention Rate, Governance Mechanism, Earnings Management, Covid-19.